INFLUENCE OF THE TEACHER’S PERSONALITY ON STUDENTS’ ATTITUDE TOWARD LEARNING (International journal of artificial intelligence, 2025)
This study analyzes how teachers’ personal and psychological characteristics affect students’ learning attitudes and motivation. The findings reveal that empathy, fairness, and enthusiasm are crucial personality traits that promote academic interest and emotional well-being.